The effect of grain size on Gmax of a demolished structural concrete: A study through energy dispersive spectroscopy analysis and dynamic element testing. Issue 89 (October 2016) - He, H.; Senetakis, K.
Abstract: Recycled concrete aggregate (RCA) composed of demolition-crushed structural concrete is a promising material in geotechnical engineering applications, for example, as a backfill in retaining walls or as an embankment fill and pavement construction material. Due to the presence of cement mortar component, RCA has a lower unit weight than that of typical soils, thus its use may be considered beneficial in engineering infrastructures with a demand in the reduction of settlements or lateral earth pressures. In this study, a set of torsional resonant column and bender element tests were carried out on uniform fractions of a recycled concrete aggregate with origin from New South Wales, Australia, with varying the mean grain size. The created in the laboratory samples, were prepared in a dry state and tested under isotropic conditions of the confinement varying the effective confining stress from 25 to 800 kPa in a resonant column and in a triaxial apparatus with embedded piezo-element inserts with a particular focus on the elastic stiffness Gmax . The results showed that the sensitivity of Gmax to pressure increased with decreasing mean grain size. This observed trend was attributed, partly, to the higher cement mortar component for fractions with a smaller grain size. The different composition of the fractions was verified through Scanning Electron Microscope - Energy Dispersive Spectroscopy (SEM-EDS) analysis in particular quantifying the ratio of Silicon over Calcium contents. The performance of expressions proposed in the literature for the prediction of Gmax of sands and gravels, was rigorously evaluated by means of measured against predicted elastic stiffness for all the fractions as well as by means of the state parameter for a particular RCA fraction. Highlights: Recycled concrete aggregate varying the mean grain size was examined in the study. Resonant column and bender element tests were performed on dry samples. The shape of the grains was quantified by means of the regularity descriptor. SEM-EDS analysis was conducted to investigate the cement inclusion. The results showed a higher sensitivity of Gmax to pressure with a decrease of d50 .